Study of Integrated Pest Management Strategy on The Population of Fruit Flies (Bactrocera spp.) in Red Chili Cultivation (Capsicum Annuum) - Muhlison, Wildan; Haryadi, Nanang Tri; Kurnianto, Agung Sih; Ahmada, Bugar Syarif (The Journal of Experimental Life Science, 2021)
The fruit fly Bactrocera spp. is the main pest other than Thrips in red chilies, which can reduce plant productivity by 30-60%, so that a specific method of handling this pest is needed. This study examines the application of conventional and Integrated Pest Management (IPM) strategies to fruit fly populations in red chili cultivation (Capsicum annuum). Observation of fruit fly population used the comparative method with methyl eugenol traps and incubation of infected fruit. Determination of the research sample based on purposive sampling method and analyzed using descriptive analysis. The test parameters were the fruit fly population indicated by the host's density and hosts' availability in the applied IPM and conventional treatments. The results showed that the fruit fly species encountered were dominated by B. dorsalis with a percentage of 98.18% and B. carambola 1.82%. The fruit fly population's fluctuation in IPM and conventional treatments were significantly different, as evidenced by a one-way variance test at a significance level of 99%. The population of fruit flies in the IPM concept was 547 flies, while the conventional concept was 1546 flies. The percentage of fruit fly population in red chili plants with IPM treatment was 48% smaller than conventional treatments.Keywords: Bactrocera spp., IPM, Population, Red chilies.